Study of preservation solutions by comparing Dimethyl Sulfoxide – Sodium Chloride (DMSO-Nacl) and ethanol as storage for soft tissue samples - Abdi, Dahir Ali Hersi (2022)
DNA profiling for victim identification is one of the most important aspects to consider in mass disaster identification. Proper collection, storage and preservation procedures are crucial to reduce the effect of the degradation. Therefore, the aim of this study is to assess the potential of 20%DMSO-NaCI in preserving the soft tissue sample by comparing with the ethanol solution. A total of 112 fresh beef meat were stored in 20% DMSO-NaCI, absolute ethanol, 35% ethanol and sterile deionized distilled water and incubated at ambient temperature (25-28C) and 37C until 42 days. DNA extraction of the soft muscle tissues was carried out based on the Phenol-chloroform DNA extraction method and DNA quantification was performed using a Nanodrop spectrophotometer. The statistical analysis of Variance (ANOVA) shows that there is no statistical significance between the average DNA concentration and the time of incubations (P=0.539756). The success of PCR amplification was seen in all extracted DNA for both incubation conditions and preservative solutions for up to 42 days by amplifying 120bp of cytochrome b gene. In this study, the effect of DNA degradation cannot be determined because the use of short amplicon length increased the potential for successful amplification of the target gene. In summary, the findings show that 20% DMSO-NaCI can be proposed as an alternative preservative solution for the storage of tissue samples based on the capability to retain the DNA integrity as good as ethanol.